2008
DOI: 10.5465/amp.2008.35590353
|View full text |Cite
|
Sign up to set email alerts
|

Does It Pay to Be Green? A Systematic Overview

Abstract: The conventional wisdom concerning environmental protection is that it comes at an additional cost imposed on firms, which may erode their global competitiveness. However, during the last decade, this paradigm has been challenged by a number of analysts (e.g., Porter & van der Linde, 1995), who have argued basically that improving a company's environmental performance can lead to better economic or financial performance, and not necessarily to an increase in cost. The aim of this paper is to review empirical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,169 publications
(310 citation statements)
references
References 53 publications
(43 reference statements)
8
241
0
5
Order By: Relevance
“…The size of the firm can be positively associated with the degree of environmental activity (Hofer et al, 2012) as can the degree of stakeholder interest (Jabbour et al, 2015;Tatoglu et al, 2014). Literature confirms the importance of the positioning of the 'greening' function as a key factor in improving the environmental performance of organizations (Ambec & Lanoie, 2008). Similar to Jabbour et al (2010) empirical study on manufacturing companies located in Brazil, this case study also identifies variations in the degree to which HRM activities are aligned with environmental management, as there is inconsistency in the alignment and positioning of the environmental and HR functions.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The size of the firm can be positively associated with the degree of environmental activity (Hofer et al, 2012) as can the degree of stakeholder interest (Jabbour et al, 2015;Tatoglu et al, 2014). Literature confirms the importance of the positioning of the 'greening' function as a key factor in improving the environmental performance of organizations (Ambec & Lanoie, 2008). Similar to Jabbour et al (2010) empirical study on manufacturing companies located in Brazil, this case study also identifies variations in the degree to which HRM activities are aligned with environmental management, as there is inconsistency in the alignment and positioning of the environmental and HR functions.…”
Section: Discussionmentioning
confidence: 71%
“…Research in the field of Green HRM is inter-disciplinary, drawing from organizational themes within strategic management (Aragón-Correa & Rubio-López, 2007;Boiral, 2009, Jabbour et al, 2010Schroeder, 2012), organizational performance and performance management (Clemens, 2006;Jabbour et al, 2015;Länsiluoto & Jarvenpää, 2010;Marcus & Fremeth, 2009;Ambec & Lanoie, 2008), organizational culture, employee engagement, staff development and training (Govindarajulu & Daily, 2004;Jabbour 2013b;Rothenberg, 2003;Vaccaro & Echeverri, 2010). The following literature review focuses on the two prominent areas in the Green HRM debate as identified earlier in this study: the positioning and alignment of the environment and HR function including the integration with organizational performance and Green employee engagement.…”
Section: Green Hrmmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional wisdom of green ventures, as derived from the study of large companies, tends to emphasise the benefits of going green in terms of cost-efficiency, innovation offsets, attendant revenue growth through product differen tia tion, inc rease d transp aren cy, re duce d organisational inertia, better risk management and improved relationships with external stakeholders, and the like (Ambec and Lanoie 2008;Porter and van der Linde 1995). Nevertheless, such logics often fail to apply or apply with significant qualification to their small entrepreneurial counterparts.…”
mentioning
confidence: 99%
“…5 There are many papers in the finance literature that examine the effect of environmental performance (often referred to as Corporate Social Responsibility) on firm financials. The results there are mixed; for reviews of these studies see Graff Zivin and Small (2005), McWilliams and Siegel (2000), and Stefan and Paul (2008) .…”
Section: Notesmentioning
confidence: 99%